Use of ambient lighting during colonoscopy and its effect on adenoma detection rate and eye fatigue: results of a pilot study - Hoff, Ryan T.; Mazulis, Andrew; Doniparthi, Meghana; Munis, Assad; Rivelli, Anne; Lakha, Asif; Ehrenpreis, Eli (Endoscopy International Open, 2021)
Background and study aims Adenoma detection rate (ADR) appears to decrease as the number of consecutive hours performing procedures increases, and eye strain may be a contributing factor. Ambient light may improve symptoms of eye strain, but its effects have yet to be explored in the field of gastroenterology. We aim to determine if using ambient lighting during screening colonoscopy will maintain ADRs and improve eye strain symptoms compared with low lighting.Methods At a single center, retrospective data were collected on colonoscopies performed under low lighting and compared to prospective data collected on colonoscopies with ambient lighting. Eye fatigue surveys were completed by gastroenterologists. Satisfaction surveys were completed by physicians and staff.Results Of 498 low light and 611 ambient light cases, 172 and 220 adenomas were detected, respectively (P = 0.611). Under low lighting, the ADR decreased 5.6 % from first to last case of the day (P = 0.2658). With ambient lighting, the ADR increased by 2.80 % (P = 0.5445). The difference in the overall change in ADR between first and last cases with ambient light versus low light was statistically significant (8.40 % total unit change, P = 0.01). The average eye strain scores were 8.12 with low light, and 5.63 with ambient light (P = 0.3341).Conclusions Performing screening colonoscopies with ambient light may improve the differential change in ADR that occurs from the beginning to the end of the day. This improvement in ADR may be related to improvement in operator fatigue. The effect of ambient light on eye strain is unclear. Further investigation is warranted on the impact of ambient light on symptoms of eye strain and ADR.